Effect of counterface materials on friction and wear of graphene-coated steel under dry sliding contact. (2021) - Singh, Sudesh; Verma, Pooja; Gautam, Rakesh Kumar; Tyagi, Rajnesh
Abstract: Graphene has drawn the attention of researchers across the globe due to its exceptional properties and has a great potential to reduce friction and wear in machine elements. The present investigation is aimed at exploring the effect of counterface ball materials (Si3 N4, ZrO2, and steel) on friction and wear of a multi-layer graphene coating deposited on steel using chemical vapor deposition under reciprocating sliding. Results pointed out that the graphene coating on the steel surface reduces both friction and wear against each ball material in comparison to bare steel. Contact pressure played a vital role in determining tribological performance against different counterparts. Silicon nitride ball exhibited the highest friction and wear as surfaces were subjected to maximum contact stress. However, the minimum friction coefficient was observed for steel slid against multi-layer graphene-coated steel. The higher hardness of the zirconia ball in comparison to the steel ball helped in providing minimum wear.